Dada and Surrealism : a very short introduction - Hopkins, David, 1955- (Oxford ; New York : Oxford University Press, 2004)
A stimulating introduction to the many debates surrounding the Dadaist and Surrealist movements, such as the Marquis de Sade's position as a Surrealist deity, attitudes towards the city, the impact of Freud, and attitudes towards women.
Preliminaries; Contents; List of illustrations; Acknowledgements; Introduction; 1 Dada and Surrealism: a historical overview; 2 'Rather life': promoting Dada and Surrealism; 3 Art and anti-art; 4 'Who am I?': mind/spirit/body; 5 Politics; 6 Looking back on Dada and Surrealism; References; Further reading; Dada: the main centres key individuals and events; Key Surrealist events; Key figures associated with surrealism; Index.
Includes bibliographical references (pages 157-166) and index.
Print version record.
Keywords: Dadaism; Surrealism; Arts, Modern -- 20th century; ART -- History; Arts, Modern; Dadaism; Surrealism; Dadaism; Surrealism; Arts, Modern -- 20th century; 1900-1999; Electronic books